Islamic Values-integrated Disaster Mitigation Education: A Module Development Study for Pre-Service Early Childhood Teachers - Syarfina Syarfina; Rita Mahriza (Program Studi Pendidikan Islam Anak Usia Dini, Institut Agama Islam Ma'arif (IAIMNU) Metro Lampung, 2026)
Despite Indonesia’s high disaster risk, disaster mitigation education in early childhood teacher preparation remains largely technocratic, with limited integration of faith-based perspectives that shape learners’ moral reasoning and behavioral responses. Existing studies have predominantly emphasized cognitive preparedness, leaving a gap in pedagogical models that connect disaster knowledge with spiritual and ethical dimensions. This study addresses this gap by developing an Islamic value - integrated disaster mitigation learning module for pre-service early childhood teachers. Using a Research and Development (R&D) approach based on the 4-D model (Define, Design, Develop, Disseminate), the study involved expert validation (content, media, and language) and user-based practicality testing with 32 students in an Early Childhood Islamic Education program in Aceh. The findings indicate that the module achieved a high level of validity (M = 3.75) and practicality (M = 3.72), demonstrating its feasibility and usability in instructional contexts. More importantly, the integration of Islamic values, amanah, ikhtiar, sabr, and tawakkul, functioned not merely as supplementary content but as a pedagogical framework that reorients disaster mitigation learning toward moral responsibility, ecological awareness, and reflective decision-making. Analytically, the study shows that embedding faith-based values transforms disaster education from knowledge transmission into value-driven learning, enabling pre-service teachers to conceptualize disaster preparedness as both a scientific and ethical practice. This research contributes to the field by offering an empirically validated model of faith-integrated disaster education and advancing the discourse on holistic approaches in early childhood teacher preparation. The module provides a practical and scalable resource for integrating spiritual values into disaster mitigation curricula in similar socio-religious contexts.